Analysis of living conditions contributing to child undernutrition: Evidence from literature - Om Raj Katoch (AG Volumes, 2022)
Children's nutritional status is influenced by several interacting factors that are at once and in a roundabout way related to each other and act individually or collectively. We examined the relationship between living conditions and child undernutrition in this paper. A conceptual framework of UNICEF (1990) is analysed to realize how numerous factors at one-of-a-kind degrees are accountable for child malnutrition or undernutrition. The link between maternal and child nutritional status additionally been analysed. Researchers found that malnourished children are more likely to live in homes that lack safe drinking water and toilet facilities, use open areas and traditional fuel for cooking, have undernourished mothers, and are living in homes with limited area. The governments have to intervene in those areas and educate community contributors specifically caregivers, lactating ladies, and expecting mothers, a good way to cast off the hassle of undernutrition.